Similar Images in Surah Yunus: A study in Arabic rhetoric - Abdullah, Raghad Waleed (Journal of Tikrit University for Humanities, 2020)
The purpose of the research is to identify the simulating images in Surat Younis, in order to identify the secrets and aesthetics of the rhetorical miracles and its effect on the Qur'anic interpretation and to understand some of its provisions and rules. This is because the Qur'anic text occupies an important place in the language of the nation and its heritage; it builds the features of thought in our lives by crystallizing the concept of life according to the rules characterized by linguistic maturity. Moreover, the function of Qur'an is the function of connecting it with intellectual persuasion, politeness and mentalist in addition to emotional and faithful persuasion. This confirms the superiority of the Qur'anic text over all the texts that have shown the power of Allah almighty and shows the inability of the aggressors and liars in his saying : "If the mankind and the Jinns were together to produce the like of this Quran, they could not produce the like thereof, even if they helped one another." 88, the Holy Qur'an with its wise and detailed legislation. We must understand and manage the eloquent analogies in the Holy Quran, they are analogies that illustrate the facts in the best way. The Qur'anic simile still occupies a large part in the field of research because of its lessons, sermons and superior rhetoric, so I chose the analogies in Surat Younis and analyzed them and interpreted them and state the analogy in it and state of what the analogy adds to it of the aesthetic significant and the good statement.